Cryolipolysis Does not Modify the Behavior and Recovery of Cardiac Autonomic Modulation - Toledo, Ana Clara Campagnolo Real Gonçalves; de Souza Cavina, Allysiê Priscilla [UNESP]; Seixas, Isadora Stefen [UNESP]; de Jesus, Letícia Rosa [UNESP]; Silva, Maria Eduarda Leonel [UNESP]; de Araújo, Bruna Garcia Corral; Vanderlei, Franciele Marques [UNESP] (Springer Nature, 2022)
Abstract: The desire to reduce and remodel undesirable fatty deposits has increased the popularity and use of aesthetic procedures, among them, cryolipolysis. However, repercussions on the autonomic nervous system must be considered, since the decrease in cutaneous body temperature can have repercussions on sympathetic and parasympathetic components. The aim was to evaluate the behavior of cardiac autonomic modulation during and after a single application of cryolipolysis. A single-arm, prospective interventional study evaluated data from 13 women with a mean age of 22.38 ± 2.95 years, who had an accumulation of abdominal fat of at least 1.5 mm, were using oral contraceptives, and were sedentary. A professional applied cryolipolysis in a single 40-min session. RR intervals were collected by means of a cardiofrequency meter, at rest prior to the technique for 10 min, during the performance of the technique, and immediately after the end of the technique for a period of 50 min. Heart rate variability (HRV) analysis was performed using time, frequency, and Poincaré plot indices. For the mean RR, SDNN, rMSSD, SD1, SD2, and LF [ms2] indices, the values increased during the execution of cryolipolysis when compared to rest. In the recovery period, increases in the mean values of the RR, SDNN, rMSSD, SD1, SD2, HF [ms2], LF [nu], and HF [nu] indices were also observed when compared to the baseline moment. Both during the technique and in the recovery period, there were changes in the behavior of HRV characterized by an increase in global and vagal indices. Level of Evidence IV: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.
Keywords: Aesthetic equipment; Autonomic nervous system; Esthetics; Heart rate; Heart rate variability